Palgrave Advances in Intellectual History
IX, 239 p.
Keywords: The past three decades have seen a remarkable growth of interest in intellectual history and this book provides the first comprehensive survey of recent research in this field. Each chapter considers developments in intellectual history, and shows the ways intellectual historians have contributed to more established disciplinary enquiries.